A chiral aldehyde-induced tandem conjugated addition–lactamization reaction for constructing fully substituted pyroglutamic acids. Issue 5 (3rd February 2022) - Wang, Wen-Zhe; Shen, Hao-Ran; Liao, Jian; Wen, Wei; Guo, Qi-Xiang
Abstract : A chiral aldehyde-catalyzed tandem nucleophilic addition-lactamization reaction is described. Structurally diverse fully substituted pyroglutamic acids were generated in moderate-to-good yields and stereoselectivities. Abstract : A catalytic asymmetric tandem reaction including a chiral aldehyde catalyzed conjugated addition and an intramolecular lactamization is reported in this work. Under the optimal reaction conditions, various fully substituted pyroglutamic acids bearing three vicinal chiral centers were generated in good-to-excellent yields and stereoselectivities. A reasonable reaction mechanism is proposed to illustrate the observed stereoselective control results.